One dark and scary night. - Cosby, Bill, 1937 (New York : Scholastic Inc, 1999)
One night Little Bill is convinced there are mean things in his dark closet and that they are just dying to get him. Only when Alice the Great performs a magical tucking-in trick do the mean things go away for good.
Keywords: Fear of the dark-Fiction; Great-grandmothers-Fiction; Afro-Americans-Fiction